Separation of Thorium (Th) from Monazite Sand of Bangka Island using Primene JMT Solvent Extraction Method - Claudia, Dita; Fabiani, Verry Andre; Nurhadini, Nurhadini; Prassanti, Riesna (Badan Riset dan Inovasi Nasional, 2023)
Thorium is an essential element as an alternative nuclear fuel to replace uranium. Thorium is found in the mineral monazite, which is a by-product of the alluvial tin mining process. Many methods have been used to extract and separate thorium from uranium and REEs from monazite, one of which is the organic solvent extraction method. In this research, the primene JMT, which is an extractant of primary amine compounds, was used in the method. The studied parameters are feed pH, JMT primene concentration, and stirring speed. The results show that the optimum conditions for Th extraction in monazite using solvent extraction method primene JMT were obtained at pH 0.5, extractant concentration of 2%, and stirring speed of 300 rpm with Th recovery of 94.05% while U and REE were not extracted.